The Challenge in Combining Pelotherapy and Electrotherapy (Iontophoresis) in One Single Therapeutic Modality - Carla Marina Bastos; Fernando Rocha; Nuno Gomes; Paula Marinho-Reis (Applied Sciences, 2022)
Pelotherapy and electrotherapy are therapeutic methodologies with proven success in physical medicine and rehabilitation (PMR) and dermatology fields. The main purpose of these therapeutic modalities is to reduce pain, accelerate wound healing, alleviate muscle spasms, and improve mobility, and muscle tone. Their main challenge is in the passage of some ionic species through the skin barrier. The use of drugs, such as diclofenac, corticosteroids or steroids, has gained widespread efficacy recognition in physical therapy and the therapeutic action of these drugs is widely studied in experimental and clinical trials. Unlike pharmaceutical and cosmetic clays, peloids are not subject to any prior quality control or subject to any specific European regulation. The dermal absorption values are an integral part of the risk assessment process for peloids. This work explores the converging points between these two transdermal drug delivery systems (TDDS) and the presentation of methodologies to achieve peloid safety compliance, especially concerning the potential and degree of toxicity arising from ion exchange and trace elements. TDDS is applied to the pharmaceuticals industry and drug is the generic term for the active substances released into skin tissues. The transdermal delivery of drugs or clay components with therapeutic properties is limited due to the excellent barrier function of the stratum corneum. The transdermal drug delivery of pelotherapy is enhanced by temperature and electrically by iontophoresis. The low voltage of iontophoresis and sweat phenomena with pore dilation driven by pelotherapy allows the use of the same pathways: hair follicles and sweat pore. The therapeutic integration of iontophoresis and pelotherapy focused on patient benefits and low safety-related risk may contribute to the outstanding physiological performance of pelotherapy, specifically, in the way the essential elements and exchange cations pass through the skin barrier. The validation of an innovative iontophoretic systems applied to pelotherapy can also promote future challenges in the obtaining of the ideal therapeutic control of peloids and the clinical validation of results with physiological efficacy recognition.